ADAMTS-13 activity reduction in plasma of acute myeloid leukemia predicts poor prognosis after bone marrow transplantation. Issue 1 (1st January 2019) - Liu, Chen; Han, Man; Zhao, Lei; Zhu, Mengjie; Xu, Qinzhu; Song, Ying; Wang, Hui
ABSTRACT: Objective: This research aimed to explore the significance of low activity of ADAMTS-13 in acute myeloid leukemia (AML) after bone morrow transplantation (BMT), and to evaluate the disease progress and prognosis of the patients with low or normal activity of ADAMTS-13 after BMT. Methods: 46 AML patients were included in our research. ADAMTS-13 activity was measured before BMT. Their medical indicators were recorded one month after BMT. All the patients were followed up and their disease progression was evaluated afterwards. The medical indicators and prognosis situation were compared between Low ADAMTS13 Group (<481 ng/ml) and Normal Group (481–785 ng/ml) according to the reference range of local laboratory. ROC curves were used to evaluate the predictive value of ADAMTS13 for infection complications and survival. Results: Low ADAMTS13 Group show extended APTT, PT and elevated CRP and D-Dimer levels, compared with Normal Group. Low ADAMTS13 Group suffered more BMT-related complications than Normal Group. In addition, Low ADAMTS13 Group underwent higher mortality than Normal Group in the one-year follow up after BMT and two-year follow up after onset of AML. ADAMTS13 has AUC of 0.7675, 0.7254, 0.8019 for lung infection, CMV infection and death within one year after BMT, suggesting that ADAMTS13 has predictive value for prognosis of AML patients after BMT. Discussion: For patients with low ADAMTS13 activity, the prognosis was worse and the probability of serious complications and mortality was significantly higher than AML patients with normal ADAMTS13 activity, which suggest predictive role of ADAMTS13 activity for the prognosis of AML after BMT. Conclusion: AML patients with low activity of ADAMTS-13 had worse prognosis after BMT.